Peran Masayarakat Dalam Penegakan Hukum Lingkungan. - Kunarto, Kunarto; Budi Prasetyo (Universitas Sains dan Teknologi Komputer, 2023)
Environmental law enforcement cannot be implemented properly, this is because environmental law material contains various legal materials and norms that differ in perception, so that the impression appears as if they are unable to carry out the legal function properly and correctly. The emergence of various environmental problems is clear evidence of the inability to enforce environmental law as outlined in the law, one of the reasons is the lack of community participation in enforcing environmental law. Related to this, problems arise, what is the role of society in enforcing environmental law, as well as the obstacles faced in enforcing environmental law. To answer this problem, there needs to be consistency from various parties related to environmental law enforcement itself, starting from statutory regulations, implementing officials and community participation. The community has an important role in enforcing environmental laws, therefore the community needs to be invited to continue to monitor and report various forms of violations of the environment and existing natural resources. The community has duties and obligations in enforcing and managing the environment, this is because they are parties affected by the development process which often has an impact on environmental sustainability. Realizing the importance of community involvement in environmental protection and management, Law no. 32 of 2009 concerning Environmental Protection and Management (UUPPLH) has also provided several general provisions for the public to proceed in court using the right to sue representatives, as regulated in Articles 90 to 92 of the law. On this basis, the community can play an active role in enforcing environmental laws. With a model of community control and supervision, violators can be careful in carrying out activities that can pose environmental risks, it is through the community that supervision can also be carried out, so that the environment can be preserved and intact.